2013
DOI: 10.1016/j.drugalcdep.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Methadone and buprenorphine-naloxone are effective in reducing illicit buprenorphine and other opioid use, and reducing HIV risk behavior—Outcomes of a randomized trial

Abstract: Aims Determine the extent to which buprenorphine injectors continue treatment with buprenorphine-naloxone or methadone, and the impact of these treatments on substance use and HIV risk in the Republic of Georgia. Methods Randomized controlled 12-week trial of daily-observed methadone or buprenorphine-naloxone followed by a dose taper, referral to ongoing treatment, and follow-up at week 20 at the Uranti Clinic in Tbilisi, Republic of Georgia. Eighty consenting treatment-seeking individuals (40/group) aged 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 35 publications
(38 reference statements)
2
39
1
1
Order By: Relevance
“…The oral opioid analgesics methadone [MET; (RS)-6-(dimethylamino)-4,4-diphenylheptan-3-one] and buprenorphine {BUP; (2S)-2-[(5R,6R,7R,14S)-9␣-cyclopropylmethyl-4,5-epoxy-6,14-ethano-3-hydroxy-6-methoxymorphinan-7-yl]-3,3-dimethylbutan-2-ol} are evidence-based treatments for opioid dependence and are a staple in the management of this addiction (9)(10)(11). MET is a chiral compound normally administered as an RS racemic mixture of which most or all opioid activity resides with R-MET (12,13).…”
Section: T Reatment Of Chronic Hepatitis C Virus (Hcv) Infection Hasmentioning
confidence: 99%
“…The oral opioid analgesics methadone [MET; (RS)-6-(dimethylamino)-4,4-diphenylheptan-3-one] and buprenorphine {BUP; (2S)-2-[(5R,6R,7R,14S)-9␣-cyclopropylmethyl-4,5-epoxy-6,14-ethano-3-hydroxy-6-methoxymorphinan-7-yl]-3,3-dimethylbutan-2-ol} are evidence-based treatments for opioid dependence and are a staple in the management of this addiction (9)(10)(11). MET is a chiral compound normally administered as an RS racemic mixture of which most or all opioid activity resides with R-MET (12,13).…”
Section: T Reatment Of Chronic Hepatitis C Virus (Hcv) Infection Hasmentioning
confidence: 99%
“…26 This may reflect that active daily users have failed other pharmacologic treatment options and are interested in exploring new therapies. Although several pharmacologic options already exist for the treatment of opioid addiction, including methadone, buprenorphine, and extended release naltrexone, 2,4,5,7,8,35 these options do not sustain abstinence in all users, 36 necessitating continued research into new medications and different formulations of existing ones. No approved pharmacologic treatment options presently exist for stimulant use disorders 1416 and it is therefore unsurprising that individuals engaged in frequent crack-cocaine use would be eager to participate in drug treatment trials.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report data from a study in which opioid addicted Subutex® injectors were randomized to a 12-week course of dailyobserved Suboxone® or methadone and discuss possible reasons for the low level of drug use during OST in Georgia as compared to the U.S. Study details and the primary outcomes of opioid use and HIV risk have been reported elsewhere (Otiashvili et al, 2013). Conclusions were that daily observed methadone or buprenorphine-naloxone treatments were effective for non-medical buprenorphine or other opioid use and likely to be useful for preventing HIV infection.…”
Section: Introductionmentioning
confidence: 97%
“…Information about the impact of OST on opioid and non-opioid use is particularly important in a country such as Georgia that has a very low prevalence of HIV (Otiashvili et al, 2013) but is geographically close to Former Soviet States where injecting opioid use is contributing to one of the most rapidly growing HIV epidemics in the world (Bobrovsky et al, 2012;Carrieri et al, 2006). Though HIV prevalence has been low in Georgia, the prevalence of Subutex® injection and sharing of injection equipment has been high during the last decade as Subutex® was commonly smuggled in from France (Gamkrelidze et al, 2004;Javakhishvili et al, 2006).…”
Section: Introductionmentioning
confidence: 99%